Kepercayaan Diri dan Kecemasan Komunikasi Interaktif pada Siswi yang Tinggal di Asrama - Tiara Putri Prastiwi (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
Anxiety in interactive communication refers to an individual's negative reaction when communicating, especially in an interpersonal context, where individuals tend to avoid situations that trigger these negative feelings. Positive self-confidence allows a person to assess themselves and situations more positively, thereby reducing anxiety in interpersonal communication. This study aims to explore the relationship between self-confidence and interactive communication anxiety in female students living in dormitories. Data was collected using the Self-confidence scale and interpersonal communication anxiety scale, which have been well validated and have a high level of reliability. The results of the analysis show that there is a significant negative relationship between self-confidence and interactive communication anxiety (rxy = -0.608, sig. = 0.000 < 0.05), indicating that the higher the female student's self-confidence, the lower the level of interpersonal communication anxiety. Descriptive analysis also shows that most of the female students in the dormitory have a moderate level of self-confidence, while most of them have a low level of interactive communication anxiety.